2019
DOI: 10.1108/hff-03-2019-0273
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluid flow and heat transfer due to natural convection in a semi-circle/ellipse annulus using modified lattice Boltzmann method

Abstract: Purpose This paper aims to numerically investigate the nanofluid flow, heat transfer and entropy generation during natural convection in an annulus. Design/methodology/approach The lattice Boltzmann method is used to simulate the velocity and temperature fields. Furthermore, some special modifications are applied to make the lattice Boltzmann method capable for simulation in the curved boundary conditions. The annulus is filled with CuO-water nanofluid. The dynamic viscosity of nanofluid is estimated using K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The findings depicted that both the total EG rate and the Bejan number augment with the rise of 𝑅𝑎. In a numerical investigation, Xiong et al [31] studied the free convection of water-CuO NF in a semi-circle/ellipse annulus using modified lattice Boltzmann method. The aim of this numerical assessment is to evaluate the free convection flow of a non-Newtonian nanofluid (NF) inside an eccentric horizontal annulus from the point of view of first-law and second-law of thermodynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings depicted that both the total EG rate and the Bejan number augment with the rise of 𝑅𝑎. In a numerical investigation, Xiong et al [31] studied the free convection of water-CuO NF in a semi-circle/ellipse annulus using modified lattice Boltzmann method. The aim of this numerical assessment is to evaluate the free convection flow of a non-Newtonian nanofluid (NF) inside an eccentric horizontal annulus from the point of view of first-law and second-law of thermodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In a numerical investigation, Xiong et al. [31] studied the free convection of water‐CuO NF in a semi‐circle/ellipse annulus using modified lattice Boltzmann method.…”
Section: Introductionmentioning
confidence: 99%
“…Although more velocities of the lattice will occupy more memory and require higher computing requirements, considering the numerical stability and accuracy of turbulent flow, the D3Q27 velocity space discrete scheme was used in this study, as shown in Figure 2. By discretizing the Boltzmann equation in velocity space, physical space, and time, the lattice Boltzmann equation is given as [23] ,…”
Section: Lattice Boltzmann Methodsmentioning
confidence: 99%
“…Eslam performed a numerical simulation for studying the vorticity dynamics of a dipole colliding with the wall in a bounded flow and the wake structure and separated flow properties past a circular cylinder at the values of Reynolds numbers with LBM (Eslam Ezzatneshan, 2020). Xiong et al (2019) numerically investigate the nanofluid flow, heat transfer and entropy generation during natural convection in an annulus with LBM. The migration and deposition of microparticles in porous media were numerically simulated with the LB method by Lei et al , 2017.…”
Section: Introductionmentioning
confidence: 99%